Evaluation of spaceborne GNSS-R based sea surface altimetry using multiple constellation signals - Cheng, Zixuan; Jin, Taoyong; Chang, Xin; Li, Yunwei; Wan, Xiangcheng (Frontiers in Earth Science, 2023)
Comparisons between different Global Navigation Satellite Systems (GNSS) signals and GNSS-Reflectometry (GNSS-R) satellite systems can provide valuable suggestions for future development of GNSS-R instrument and signal processing method. This article evaluates the ocean altimetry performance of multiple GNSS constellation signals using raw Intermediate Frequency data collected by Cyclone GNSS (CYGNSS) and TechDemoSat-1 (TDS-1) satellites. Data used for the evaluation includes observations of GPS L1, Galileo E1, BDS B1 band signal. The specular point position and the ground-truth bistatic delay are calculated through HALF method. After corrections of ionospheric, tropospheric and tide, the sea surface height can be retrieved; and then the height is compared with DTU18 mean sea surface model derived one. Based on the GNSS-R satellite collected observations, an optimal incoherent integral duration is determined. By making use of the optimal duration, the CYGNSS based ranging delay estimating accuracy improves to 2.48m, 2.57m, and 2.15m for GPS, Galileo and BDS respectively; and the TDS-1 based one improves to 6.81m and 5.74m for GPS and Galileo respectively. The results can provide suggestion on the strategies of multi-constellation observations fusion to improve the altimetry accuracy.